Two Variants in the NOTCH4 and HLA-C Genes Contribute to Familial Clustering of Psoriasis - Minglong Cai; He Huang; Zhulin Hu; Tao Yuan; Weiran Li; Yaoguang Liu; Lijun Zheng; Yan Zhang; Yujun Sheng; Xuejun Zhang (International Journal of Genomics)
Psoriasis is a multifactorial immune-mediated skin disease with a strong genetic background. Previous studies reported that psoriasis with a family history (PFH) and sporadic psoriasis (SP) have a distinct manifestation and genetic predisposition. However, the genetic heterogeneity of PFH and SP in the major histocompatibility complex (MHC) region has not been fully elucidated. To explore genetic variants in the MHC region that drive family aggregation of psoriasis, we included a total of 8,127 psoriasis cases and 9,906 healthy controls from Han Chinese and divided psoriasis into two subtypes, PFH (n=1,538) and SP (n=5,262). Then, we calculated the heritability of PFH and SP and performed a large-scale stratified association analysis. We confirmed that variants in the MHC region collectively explained a higher heritability of PFH (16.8%) than SP (13.3%). Further stratified association analysis illustrated that HLA-C∗06:02 and NOTCH4:G511S contribute to the family aggregation of psoriasis, and BTNL2:R281K specifically confers risk for SP. HLA-C∗06:02 and NOTCH4:G511S could partially explain why patients with PFH have a stronger genetic predisposition, more complex phenotypes, and more frequent other autoimmune diseases. The identification of the SP-specific variant BTNL2:R281K revealed that the genetic architecture of SP is not just a subset of PFH.